A CMUT-based gas density sensor with high sensitivity. (18th September 2019) - Zhao, Libo; Li, Jie; Li, Zhikang; Zhao, Yihe; Luo, Guoxi; Xu, Tingzhong; Guo, Shuaishuai; Liu, Zichen; Wang, Jiuhong; Jiang, Zhuangde
Abstract: In this paper, a gas density sensor based on capacitive microfabricated ultrasonic transducers (CMUTs) is developed. The working principle is based on the resonant frequency shift of the membrane by the change of gas density under the fluid-solid interaction. Due to the advantages of high frequency, the frequency shift will be larger, which also results in higher detection measuring sensitivity (DMS). Combined with the fluid added mass model and the electromechanical coupling reduced order model of a CMUT in vacuum, the relationship between gas density and resonant frequency is established. Furthermore, the influences of the structural parameters and the bias voltage on DMS are further analyzed. As a result, a good linearity is shown between gas density and resonant frequency of CMUTs in a certain density range. Simultaneously, the CMUT-based density sensor shows a high measuring sensitivity. After fabricating a sensor with the low-temperature direct wafer-bonding technique and building the gas density detection platform, the resonant frequency and phase-frequency curves of the CMUTs-based density sensor under different bias voltages are achieved by the experimental analysis in the different mixed gas. The results demonstrate the excellent capability of fabricated CMUTs for gas density measurement with a good linear relationship between gas density and resonant frequency and a higher DMS of 9760 Hz · kg −1 · m 3, which make it a promising sensor.